2008
DOI: 10.1007/s00520-008-0425-1
|View full text |Cite
|
Sign up to set email alerts
|

Mirtazapine improves sleep and lowers anxiety and depression in cancer patients: superiority over imipramine

Abstract: Our findings suggest that mirtazapine is effective for resolving insomnia as well as anxiety and depressive symptoms in cancer patients. However, more systematic research, such as placebo-controlled studies, is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 31 publications
0
54
0
6
Order By: Relevance
“…Among cancer patients, antidepressants are used not only to treat depression, but they also treat hot flashes, sleep disturbances, pain, and multidrug resistance [11][12][13].…”
Section: Antidepressant Usementioning
confidence: 99%
“…Among cancer patients, antidepressants are used not only to treat depression, but they also treat hot flashes, sleep disturbances, pain, and multidrug resistance [11][12][13].…”
Section: Antidepressant Usementioning
confidence: 99%
“…Effects of initial, middle, and late insomnia also improved statistically in the mirtazapine group. Study visits occurred every 2 weeks, with the most impressive results seen at the first and second visits (10). Further small studies showed benefits of mirtazapine at both the 15-mg and 30-mg daily doses against the mild symptoms of depression, loss of appetite, and decline in cognition function.…”
Section: Mirtazapinementioning
confidence: 99%
“…Alcuni studi hanno valutato l'efficacia di mirtazapina (Tabella I) in pazienti affetti da patologia neoplastica maligna che presentavano sintomi depressivi, nausea, vomito, perdita dell'appetito, insonnia e numerosi sintomi algici [20][21][22].…”
Section: Disclosureunclassified